Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan PT PLN (Persero) UP3 Makassar Utara - Yohanis Yohanis; Rilfan Kasi’ Rantetadung; Muhammad Basri; Meriani Nippi (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the effect of job training on the performance of PT PLN (Persero) UP3 MAKASSAR UTARA employees. The method used was a survey by distributing questionnaires to 50 respondents. The collected data will be analyzed using linear regression analysis to determine how much influence job training has on employee performance variables. The research results show that job training has a positive and significant effect on employee performance. It is hoped that this research will contribute to improving employee performance by improving job training. Apart from that, the results of this research can also provide guidance for companies in managing employees better, so that companies can increase overall productivity and efficiency.